Pengembangan Sistem Informasi Pelayanan dan Pendataan UMKM Provinsi Riau (Studi Kasus: Dinas Perindustrian, Perdagangan, Koperasi Usaha Kecil dan Menengah Provinsi Riau) - Muhamad Guntur Dermawan Amin; Adam Hendra Brata; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Riau Province Department of Industry, Trade, Cooperatives, Small and Medium Enterprises is a government agency that organizes programs related to industry, trade, cooperatives, small and medium enterprises in Riau Province. DISPERINDAGKOP UKM Riau Province has a UPT PLUT KUMKM which is tasked with collecting data and services for UMKM players in Riau Province which are still done manually. Then a service information system and data collection was developed using the waterfall model method. The system can be used by the community, MSME actors, and local governments, has the main features for product management, service, and data verification for MSME actors that apply optical character recognition to extract ID card data. This system has 25 functional requirements and 1 non-functional requirement. This system was developed using the Laravel 8 and Bootstrap 4 framework. This system was tested using unit testing, integration testing, compatibility testing, and validation testing. Based on the test results, the cyclomatic complexity value is low and the results are valid for 67 test cases in the validation test on the system that has been implemented, it is stated that the system can run well in accordance with the results of the requirements analysis and design.